Development Programme of Sergo Ordzhonikidze Russian State University for Geological Prospecting (MRGI) for 2023—2027 - Yu. P. Panov (Известия высших учебных заведений: Геология и разведка, 2022)
Russia’ national Programme for the Reproduction of the Mineral Resource Base cannot be implemented successfully without coordination between the quality of mining specialist training and the pace of developing mineral resources both in terms of solving methodological issues and providing stable funding.The Sergo Ordzhonikidze Russian State Geological Exploration University carries out its activities aimed at training specialists for organizations of the Federal Agency for Subsoil Use. This direction is elucidated in the Programme and Development Strategy of the University for 2023–2027.